ANALISIS PENDAPATAN NELAYAN BAGAN TANCAP (STICK HELD DIP NET) DAN BAGAN PERAHU (BOAT LIFT NETS) DI KAMPUNG TANJUNG BATU KECAMATAN PULAU DERAWAN - Julaila; Muhammad Syafril; Qoriah Saleha (2339-1324, 2017)
The aims of this study are: 1) to determine the fishermen's income using stationary and boat lift nets in Tanjung Batu Village, Derawan Island Sub District; 2) to examine the difference between fishermen's income that use the stationary and boat lift nets in Tanjung Batu Village, Derawan Island Sub District; 3) to identify factors influencing the difference between fishermen's income that use the stationary and boat lift nets in Tanjung Batu Village, Derawan Island Sub District. This study was conducted from October to September, 2016 in Tanjung Batu Village, Derawan Island Sub District. Sampling was taken by using disproportionate stratified random sampling with 60 respondents consisting of 30 respondents used the stationary lift net and 30 respondents used the boat lift net. Data were analyzed income analysis, method t-Test, and multiple linear regression analysis. Results showed that the fishermen's income that used the stationary lift net at IDR. 326,314,333.33 each month or average at IDR. 12,077,144.44 each month each respondent. Meanwhile, the fishermen's income that used the boat lift nets at IDR. 414,958,166.67 each month or average at IDR. 13,831,938.89 each month per respondent. Income fishermen’s stationary lift net and boat lift nets significantly different at 95% confidence level. Variable X1 (revenue) had only significantly influenced by variable Y (income).